A bibliographic review of Fagel pamphlets as presented in the online version of the TCD 1872 printed catalogue - BYRNE, JOHN GABRIEL (My University, 2010)
In 1962 E. Braches identified the following series of papamphlets, in 235 volumes, as being in the TCD Printed Catalogue: Fag. H. 1. 1-93, Fag. H. 2. 1-89 and Fag. H. 3. 1-53. H indicates the bay, 1,2,3 the shelf number and the ranges indicate the number of volumes. The database used in the the online version of the 1872 Printed Catalogue, including the Supplement, has been searched for all these pamphlets. The entries in each of the 235 volumes is listed in a file with nane equal to the shelfmark, e.g. Fag. H. 1. 13. There are 29 pamphlets which is listed in Appendix 1. One pamphlet has not been found. Each entry in the list consists of the pamphlet number and the header(the word under which the entry is listed in the printed catalogue), the title, the imprint, if any and the shelfmark or shelfmarks of the pamphlet as about half the pamphlets occur more than once, the page number of the entry in the printed catalogue and the no. of copies.
PRESENTED
Keywords: Fagel Collection; TCD Library